2009
DOI: 10.1111/j.1468-3083.2008.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Aminolevulininic acid photodynamic therapy treatment for tinea cruris caused by Trichophyton rubrum: report of 10 cases

Abstract: rare manifestation of this dermatosis. The interesting observation was the rapid development of protruding striae with the transudation of the fluid. It was probably due to a compromised dermal integrity. Some authors suggested that hormonal factors were related to critical changes in the resistance of collagen to stretch. 6 Other authors observed sequential changes of elastolysis accompanied by mast cell degranulation and influx of activated macrophages that enveloped fragmented elastic fibers. 7 The aetiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…ALA-PDT has been used in dermatology mainly for a cohort of proliferative, angiogenic, or inflammatory skin diseases such as cutaneous cancers, precancerous lesions, fungal infections, and HPV viral infections. 12-15 …”
Section: Discussionmentioning
confidence: 99%
“…ALA-PDT has been used in dermatology mainly for a cohort of proliferative, angiogenic, or inflammatory skin diseases such as cutaneous cancers, precancerous lesions, fungal infections, and HPV viral infections. 12-15 …”
Section: Discussionmentioning
confidence: 99%
“…Six out of 10 achieved mycological cure after 1–3 treatments but 3 had recurred at 8‐week follow up. The same group 79 treated 10 patients with tinea cruris (also known as ringworm of the groin or jock itch) caused by T. rubrum with ALA–PDT. Eight out of 10 patients achieved mycological cure and 4 of these remained cured at 8 weeks.…”
Section: Other Dermatologic Infectionsmentioning
confidence: 99%
“…Past clinical trials have suggested that tinea cruris, tinea pedis, and interdigital mycoses recur frequently when treated with ALA-PDT 137139. However, more recently, one clinical trial (n=30) used chemical avulsion (occlusion with urea for ten consecutive nights prior to PDT) and 20% ALA-PDT (3-hour incubation) followed by red light therapy, and demonstrated a 43.3% cure rate at 12-month follow-up, which dropped to 36.6% at 18-month follow-up 140.…”
Section: Pdt In Microbial Diseasesmentioning
confidence: 99%